Pathological and virological findings of type I interferon receptor knockout mice upon experimental infection with Heartland virus - Fujii, Hikaru; Fukushi, Shuetsu; Yoshikawa, Tomoki; Nagata, Noriyo; Taniguchi, Satoshi; Shimojima, Masayuki; Yamada, Souichi; Tani, Hideki; Uda, Akihiko; Maeki, Takahiro; Harada, Shizuko; Kurosu, Takeshi; et al. (Virus research, 2024)
Heartland virus (HRTV) causes generalized symptoms, severe shock, and multiple organ failure. We previously reported that interferon-α/β receptor knockout (IFNAR ) mice infected intraperitoneally with 1 × 10 tissue culture-infective dose (TCID ) of HRTV died, while those subcutaneously infected with the same dose of HRTV did not. The pathophysiology of IFNAR mice infected with HRTV and the mechanism underlying the difference in disease severity, which depends on HRTV infection route, were analyzed in this study. The liver, spleen, mesenteric and axillary lymph nodes, and gastrointestinal tract of intraperitoneally (I.P.) infected mice had pathological changes; however, subcutaneously (S.C.) infected mice only had pathological changes in the axillary lymph node and gastrointestinal tract. HRTV RNA levels in the mesenteric lymph node, lung, liver, spleen, kidney, stomach, intestine, and blood were significantly higher in I.P. infected mice than those in the S.C. infected mice. Chemokine ligand-1 (CXCL-1), tumor necrosis factor (TNF)-α, interleukin (IL)-12, interferon (IFN)-γ, and IL-10 levels in plasma of I.P. infected mice were higher than those of S.C. infected mice plasma. These results indicated that high levels of viral RNA and the induction of inflammatory responses in HRTV-infected IFNAR mice may be associated with disease severity.